Singapore and international law - LIM, Chin Leng (Institutional Knowledge at Singapore Management University, 2015)
Adherence to and observance of international law in Singapore foreign policy is well-known. Affirmation of the demands of international law has been a key feature of various foreign policy statements. This is unsurprising. Small states, in particular, benefit from a rule-based and rule of law-based international order. A trading nation like Singapore, in particular, thrives on a relatively predictable global environment. International legal rules help to foster such an environment.